ORANG DENGAN GANGGUAN JIWA DAPAT MENYEBABKAN SEORANG BERPOTENSI MELAKUKAN BUNUH DIRI - kharisma argunawan (Fakultas Dharma Duta, 2020)
Mental disorders are psychological or behavioral patterns that are generally related to mental disorders or mental disorders that are not considered as a normal human development. Mental disorders according to the Islamic religion the development of self-potential in humans in the context of devotion to Allah SWT and his religion to get a calm and happy soul with the perfection of faith in worship. Therefore our aim is to conduct research 1) to find out the cause of an increase in mental illness cases 2) to find out the causes and factors in mental disorders 3) to provide solutions in cases of mental disorders.